Span-wise correlation of wind-induced fluctuating forces on a motionless flat-box bridge deck. Issue 156 (September 2016) - Yan, Lei; Zhu, Le Dong; Flay, Richard G.J.
Abstract: A detailed wind tunnel test has been carried out on a motionless flat-box bridge deck model with three special grid-generated wind fields using an electronically scanned pressure transducer system, enabling almost instantaneous capture of 372 pressure tap signals from 6 sections of 62 different spacing taps at each section. A very complete analysis has been performed on the pressure signals, and fluctuating forces through weighted integrations of pressure at each section were formed. The integral scales of fluctuating force were found to be dependent mainly on the integral scale of turbulence and the size of deck. The root coherence of buffeting force relied chiefly on integral scales of force and the separation of two sections, and the span-wise correlation of the fluctuating forces were larger than those of wind turbulence. An empirical model of root coherence for the fluctuating lift for a flat-box deck has been developed and proved to be feasible and effective for fitting the test data. The fitted parameters can be defined by simple expressions related to the oncoming turbulence and the size of deck, and thus it has practical applications. The proposed model can fully explain the character of low frequency curves in the root coherence. Highlights: The span-wise correlation of forces are larger than those of wind turbulence. Integral scales of force depend mainly on turbulence integral scales and deck sizes. Lift root coherence models explain low frequency curves with physical meanings.